2021
DOI: 10.3390/ani11102990
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Behaviour in African Elephants during Introduction into a New Group: Differences between Related and Unrelated Animals

Abstract: The introduction of elephants into new groups is necessary for breeding programmes. However, behavioural studies on the reactions of these animals at first encounters are missing. In the present study, female African elephants (Loxodonta africana) living in zoos were observed during unifications with unfamiliar elephants (introduction of two to one females and one to two females; n = 6) and reunifications with related elephants (two mother–daughter-pairs; n = 4) that were separated for 2 and 12 years, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 56 publications
(118 reference statements)
0
6
0
Order By: Relevance
“…At the moment, the low number of published papers dealing with (re)unions is unlikely to represent a high percentage of the actual cases of (re)unions taking place in zoological institutions worldwide. Moreover, published papers tend to deal mainly with highly charismatic social species (such as social primates, wild dogs and elephants [3,[12][13][14][15]), although solitary species can also be kept in groups or pairs in zoos, and such an approach has been found to be beneficial for at least some of them [8,[16][17][18][19]. For example, a quick search on Scopus (https://www.scopus.com/; accessed on 16 November 2021) with the introduction AND zoo AND cat AND social AND group as keywords rendered only one result: a paper on enrichment in tigers, including a general section on social housing [20], although two cases of a semiochemical being used during the introduction of tigers have been published elsewhere [2,21].…”
Section: Introductionmentioning
confidence: 99%
“…At the moment, the low number of published papers dealing with (re)unions is unlikely to represent a high percentage of the actual cases of (re)unions taking place in zoological institutions worldwide. Moreover, published papers tend to deal mainly with highly charismatic social species (such as social primates, wild dogs and elephants [3,[12][13][14][15]), although solitary species can also be kept in groups or pairs in zoos, and such an approach has been found to be beneficial for at least some of them [8,[16][17][18][19]. For example, a quick search on Scopus (https://www.scopus.com/; accessed on 16 November 2021) with the introduction AND zoo AND cat AND social AND group as keywords rendered only one result: a paper on enrichment in tigers, including a general section on social housing [20], although two cases of a semiochemical being used during the introduction of tigers have been published elsewhere [2,21].…”
Section: Introductionmentioning
confidence: 99%
“…A prerequisite to further explore these means is the knowledge of elephant stress levels during (re-)unification. The results of this study indicate that the fecal sample presentation did not induce an increase in physiological stress, expressed in the level of glucocorticoids, and can be a potentially useful test in advance of future (re-)unification [21,22].…”
Section: Discussionmentioning
confidence: 74%
“…In a joint study, Hörner et al [22] confirmed the positive reaction to the presentation of a relative during the re-unification of mothers and their daughters. However, unrelated elephants living in zoos reacted with tension and agonistic behavior during first encounters as part of unification.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations